Pengaruh Kepuasan Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Dengan Komitmen Organisasional Sebagai Variabel Intervening Pada PDAM Kota Padang - Gina Puspita Ayu; Laila Izzatul Rahmah; Dwi Intan Maysyaroh (CV. ITTC INDONESIA, 2024)
The aim of this research is to analyze the influence of job satisfaction and work motivation on employee performance with organizational commitment as an intervening variable at PDAM Kota Padang. The population in this study was all PDAM Padang City employees, totaling 385 people. The sample in this study amounted to 150 people who were determined using the Slovin formula. The sampling technique used was proportionate stratified random sampling. Data collection was carried out by distributing questionnaires. Data analysis uses Partial Least Square (PLS). The research results show that: (1) Job satisfaction has a positive and significant effect on employee performance; (2) Work motivation has a positive and significant effect on employee performance; (3) Job satisfaction has a positive and significant effect on organizational commitment; (4) Work motivation has a positive and significant effect on organizational commitment; (5) Organizational commitment has a positive and significant effect on employee performance; (6) Organizational commitment mediates the effect of job satisfaction on employee performance; and (7) Organizational commitment mediates the influence of work motivation on employee performance.